2021
DOI: 10.1111/tpj.15216
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of CYC2g is responsible for the evolutionary shift from radiate to disciform flowerheads in the Chrysanthemum group (Asteraceae: Anthemideae)

Abstract: Evolutionary shifts among radiate, disciform and discoid flowerheads have occurred repeatedly in a number of major lineages across the Asteraceae phylogeny; such transitions may also appear within evolutionarily young groups. Although several studies have demonstrated that CYC2 genes partake in regulating floral morphogenesis in Asteraceae, the evolution of capitulum forms within a recently diverging lineage has remained poorly understood. Here, we study the molecular regulation of the shift from a radiate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 83 publications
0
38
0
Order By: Relevance
“…This suggests that capitulum polymorphism had long existed in the ancestral populations of the Chrysanthemum-group. Comparing the present multilocus coalescent tree and the tree based on CYC2g sequences of Chrysanthemum-group (Shen et al, 2021), we found a high consensus of topologies, implying that the evolution of this group is linked to the alteration of flowerhead morphology (Supplementary Figure 7). Within Chrysanthemum-group, low pairwise niche overlaps were found between subclades, although they diverged rather recently (Figures 4, 5).…”
Section: Chrysanthemum-groupmentioning
confidence: 67%
See 4 more Smart Citations
“…This suggests that capitulum polymorphism had long existed in the ancestral populations of the Chrysanthemum-group. Comparing the present multilocus coalescent tree and the tree based on CYC2g sequences of Chrysanthemum-group (Shen et al, 2021), we found a high consensus of topologies, implying that the evolution of this group is linked to the alteration of flowerhead morphology (Supplementary Figure 7). Within Chrysanthemum-group, low pairwise niche overlaps were found between subclades, although they diverged rather recently (Figures 4, 5).…”
Section: Chrysanthemum-groupmentioning
confidence: 67%
“…This could be due to incomplete lineage sorting of genes analyzed here. We found that the sequences of their CYC2g genes were highly similar to those of A. parviflora (Shen et al, 2021; Supplementary Figure 7) which is a member distributed in the eastern part of the range of Ajania. However, the mix-up of three Ajania species with Chrysanthemum is more likely due to secondary contacts as we found all three species are polyploids with high ploidy levels from 2n = 6x to 8x and to 10x, suggesting complicated origins probably involving parentages from Ch.…”
Section: Chrysanthemum-groupmentioning
confidence: 74%
See 3 more Smart Citations